The species of the genus Azamora Walker, 1858 whose larvae feed on Passiflora sp. (Passifloraceae) in Tropical America (Lepidoptera: Pyralidae, Chrysauginae) - Vitor O. Becker (SHILAP, 2023)
Three species of the genus Azamora Walker, 1858: A. sororia Druce, 1899, A. penicillana (Walker, 1863) and A. flammeana (Sepp, [1844]), have been found to feed on Passiflora species (Passifloraceae) in Tropical America. Adults and genitalia of the three species are illustrated.